Makassar Wuling Car Marketing Strategy - Wahyudin Rahman; Asmita Wulansari Dg. Liwang (Sekolah Tinggi Ilmu Ekonomi Pariwisata Indonesia Semarang, 2023)
This study focuses on marketing activities connected to advertising tactics in order to maximize the efficacy of advertising in influencing purchase choices. The purpose of this study is to collect empirical information on the efficacy of Wuling automobile advertising and advertising effectiveness indicators that impact Wuling car purchase choices. This study employed a descriptive analysis technique as well as quantitative analysis methods such as the EPIC model and multiple linear regression. The results of the analysis using the EPIC model show that Wuling car advertising is in the effective scale range, and statistical tests show that indicators of advertising effectiveness, namely advertising messages, brand recognition, consumer trust, and consumer attitudes, have a significant effect on purchasing decisions, then partially the indicators -Indicators of advertising effectiveness have a significant effect on Wuling car purchasing decisions. Meanwhile, consumer sentiments have a negative yet considerable effect on Wuling automobile purchase choices.